Discovery of Highly Active Recombinant PNGase H+ Variants Through the Rational Exploration of Unstudied Acidobacterial Genomes - Guo, Rui-Rui; Comamala, Gerard; Yang, Huan-Huan; Gramlich, Marius; Du, Ya-Min; Wang, Ting; Zeck, Anne; Rand, Kasper Dyrberg; Liu, Li; Voglmeir, Josef (Frontiers in Bioengineering and Biotechnology, 2020)
Peptide-N4-(N-acetyl-β-glucosaminyl) asparagine amidases (PNGases, N-glycanases, EC 3.5.1.52) are indispensable tools in releasing N-glycans from glycoproteins. So far, only a limited number of PNGase candidates are available for the structural analysis of glycoproteins and their glycan moieties. Herein, a panel of 13 novel PNGase H+ candidates (the suffix H+ refers to the acidic pH optimum of these acidobacterial PNGases) was tested in their recombinant form for their deglycosylation performance. One candidate (originating from the bacterial species Dyella japonica) showed superior properties both in solution-phase and immobilized on amino-, epoxy- and nitrilotriacetate resins when compared to currently acidic available PNGases. The high expression yield compared to a previously described PNGase H+, broad substrate specificity, and good storage stability of this novel N-glycanase makes it a valuable tool for the analysis of protein glycosylation.